A review of vascular disrupting agents as a concomitant anti-tumour modality with radiation. Issue 3 (2nd May 2013) - Tran, William Tyler; El Kaffas, Ahmed; Al-Mahrouki, Azza; Gillies, Carol; Czarnota, Gregory Jan
Abstract: Background: Tumour vasculature plays an important role in the development, maintenance and sustainability of a tumour. Endothelial cells which are recruited into the tumour stroma facilitate the formation of essential blood vessels that deliver nutrients and oxygen to tumour cells. A growing body of research is showing that there are synergistic anti-tumour effects when anti-vascular agents are combined with radiation. More recent reports have described favourable radiation response as a function of vascular targeting and blood vessel breakdown, primarily through interactions of radiation with vascular endothelial cells. Vascular disrupting agents are being utilised in several forms that include molecular targeting, biophysical assault and biological interference. Purpose: In the present review, we examine current advances in anti-vascular agents to enhance tumour response when combined with radiation therapy. Methods: A comprehensive literature search was conducted on the US National Library of Medicine, National Institutes of Health (PubMed) using the following search keywords: vascular disrupting agents, radiation sensitisation, anti-angiogenic therapy, anti-vascular therapy, radiation therapy. Conclusion: Current research suggests the applicability of vascular disrupting agents as an effective radiation sensitisation agent. Pre-clinical and clinical trials have been well developed to form the theoretical framework to apply this powerful modality to the treatment of cancer.